Suivi du premier cas d’infection à Mycobacterium Ulcerans confirmé par culture, PCR et Génotypage en République Du Congo-Brazzaville - Kibadi, K. (2008)
This article presents follow-up data from the first patient in whom Mycobacterium ulcerans infection (MUI) was documented by PCR, genotyping and culture in the Republic of Congo-Brazzaville. Findings show the importance of regular clinical and microbiological evaluation for the disseminated form of the disease. The patient was probably infected in Pointe Noire where MUI has been described but never documented. Culture of specimens collected before antibiotic treatment showed that the bacterium was sensitive to the antibiotics being administered (streptomycin and rifampin) and was identical to isolates from Atlantic-coast regions of West Africa where MUI is endemic. The patient was treated with streptomycin and rifampin for 12 weeks in association with surgery. During treatment clinical examination was performed every day and microbiological analysis every two weeks. The duration of follow-up from the end of specific antibiotic treatment was 26 months. Medical treatment failed to prevent bone involvement and fistulae that were treated by surgery. However medical treatment may have limited dissemination of the disease. Serial microbiological evaluation was useful to detect bone involvement in this patient, but persistent positive gene amplification is not a proof of active disease. This study confirms that MUI is still endemic in the region of Pointe Noire. This finding underlines the need to optimize epidemiologic surveillance, laboratory diagnostic capabilities, and therapeutic management in the Republic of Congo-Brazzaville.